2006
DOI: 10.1037/0033-2909.132.1.98
|View full text |Cite
|
Sign up to set email alerts
|

A review of sex differences in peer relationship processes: Potential trade-offs for the emotional and behavioral development of girls and boys.

Abstract: Theory and research on sex differences in adjustment focus largely on parental, societal, and biological influences. However, it also is important to consider how peers contribute to girls' and boys' development. This paper provides a critical review of sex differences in: several peerrelationship processes, including behavioral and social-cognitive styles, stress and coping, and relationship provisions. Based on this review, a speculative peer-socialization model is presented that considers the implications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

157
1,831
18
42

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 2,009 publications
(2,107 citation statements)
references
References 226 publications
157
1,831
18
42
Order By: Relevance
“…If social conversation and self-disclosure differ between male and female college roommates, it could influence relationship development through the increased presence and opportunity for influence of complementary processes. While differences appear small in early childhood, these relationship differences increase in adolescence (Rose & Rudolph, 2006). Maccoby (1990) hypothesizes that early separation into same-sex play groups leads girls to develop a more polite and affiliative influencing style and leads boys to develop a more demanding influencing style.…”
Section: Discussionmentioning
confidence: 99%
“…If social conversation and self-disclosure differ between male and female college roommates, it could influence relationship development through the increased presence and opportunity for influence of complementary processes. While differences appear small in early childhood, these relationship differences increase in adolescence (Rose & Rudolph, 2006). Maccoby (1990) hypothesizes that early separation into same-sex play groups leads girls to develop a more polite and affiliative influencing style and leads boys to develop a more demanding influencing style.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more attention has been paid to the risks of friendships, such as those related to having deviant friends (e.g., Brendgen, Vitaro, & Bukowski, 2000) or experiencing jealousy in friendships (Parker, Low, Walker, & Gamm, 2005). In contrast to work that examines either protective or risk factors, very little attention has been paid to the idea that some friendship processes have both costs and benefits (Rose & Rudolph, 2006). Considering such processes could contribute to a more nuanced and sophisticated understanding of friendships.…”
Section: The Influence Of Friendship Processes On Adjustmentmentioning
confidence: 99%
“…For example, although some studies found no gender differences in reactive or proactive aggression (Connor et al 2003;Polman et al 2007), others found higher rates of reactive and proactive aggression in boys than in girls (Baker et al 2008;Little et al 2003;Salmivalli and Helteenvuori 2007;Salmivalli and Nieminen 2002). Boys also are more often the targets of peer victimization (Rose and Rudolph 2006) and show a slight delay in the development of theory of mind skills compared to girls (Sabbagh et al 2006). Apart from these main effects of gender, the previously cited literature provides only little indication that hypothesized associations between theory of mind, peer victimization, and reactive and proactive aggression should significantly differ for girls and boys.…”
Section: Gender Effectsmentioning
confidence: 99%